BEST Endovascular Versus Best Surgical Therapy in Patients with Critical Limb Ischemia (BEST-CLI) Trial - Raghu Motaganahalli (Radcliffe Medical Media, 2020)
The Best Endovascular versus Best Surgical Therapy in Patients with Critical Limb Ischemia trial (BEST-CLI) is an international, prospective, multicentre, multidisciplinary and pragmatic, open-label, superiority-based, comparative-effectiveness randomised controlled trial designed to address the knowledge gap in choosing the appropriate therapy for the treatment of critical limb ischaemia (CLI). This study compares the effectiveness of the best available surgical treatment with the best available endovascular treatment in adults with CLI who are eligible for both treatment options. The study has completed its enrolment phase and patients included in the study are currently being followed up to 50 months. Results of the study promise to provide us with answers to several questions regarding treatment options for patients with CLI, more recently referred to as chronic limb-threatening ischaemia.